An Analysis of Students' Grammatical Errors in Writing Descriptive Text - Germana Oreng Ritan (Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to identify the types of grammatical errors made by tenth-grade students at SMAN 1 Lewolema in writing descriptive texts and to analyse the causes of these errors. The sample consisted of 18 eleventh-grade students.The study employed a qualitative descriptive approach, utilizing observations, interviews, and document analysis. The findings revealed that students frequently made errors in sentence patterns, tenses, pronouns, prepositions, and punctuation. The most common errors were omission and addition, often attributed to the influence of students’ first language (L1) and their limited English vocabulary. The study underscores the need for targeted grammar instruction and vocabulary development to enhance students’ descriptive writing skills.